Pemanfaatan Media Sosial TikTok untuk Mendesain Materi Pendidikan Agama Islam Siswa Kelas VI SDN Kebontemu Jombang - Chofifah, Syarifatul; Sulaikho, Siti (AS-SABIQUN, 2024)
TikTok is an interactive and fun platform, so it can be used to design Islamic Religious Education (PAI) materials. Presenting PAI material that is dense, interesting and in a short time can make students more interested in the learning process. The method used in this research is a qualitative method with a case study approach. Data collection techniques in this study used observation, interviews and documentation. And data analysis is carried out using data reduction, data presentation, and conclusion drawing. The research location at SDN Kebontemu located in Kabunan Hamlet, Kebontemu Village, Peterongan District, Jombang Regency The purpose of this study is to design PAI material so that the interest in learning grade VI students at SDN Kebontemu will increase. The steps of designing pie material are 1. Choose the theme to be delivered. 2. Determine guidelines or references in accordance with the curriculum used. 3. Prepare the materials to be displayed. 4. Choose social media. 5. How to design material on TikTok social media.